«Brava Gente Brasiliana» (II): The Brasilianist Discourse and its Lexicological Misunderstandings - Santa Rosa Matos, Marcos Paulo; Souza Cruz, Itana Virginia; Faye Pedrosa, Cleida Emilia (Lingüística y Literatura, 2022)
This paper analyzes the lexicological arguments of ufanist and separatist movements in Brazil to distinguish the adjectives brasiliano and brasileiro and defend the adoption of the former one: i) the suffix –eiro denotes profession or trade, not forming gentiles and having a pejorative connotation; ii) the suffix –ano is, by excellence, the one that forms gentiles in Portuguese, similarly than in other languages. To do so, we discuss the formation of the adjective brasileiro and its use as a sign of nationality. We also investigate the morphosemantic values of the suffixes –eiro and –ano.